Optimization of Financial Management Policies in Public Service Agencies: Improving Efficiency and Accountability Based on State Treasury Law - Ahmad Habibi Rosadi; Dyah Rahmawati; Paisol Burlian (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2026)
Financial management in Public Service Agencies (BLUs) demands a critical balance between operational flexibility and strict adherence to governance standards. While the State Treasury Law mandates foundational principles such as transparency, accountability, and efficiency, practical implementation frequently stalls due to systemic oversight gaps and capacity deficits. This study aims to analyze and construct advanced optimization strategies for BLU financial management, moving beyond basic compliance to resolve persistent inefficiencies. Employing a doctrinal research method, this study evaluates legal norms, theories, and relevant policy documents. Diverging from conventional approaches, this study argues that genuine financial optimization in BLUs requires a structural paradigm shift from passive administrative compliance to an active, risk-mitigated governance ecosystem. The findings assert that operationalizing the State Treasury Law necessitates the mandatory integration of real-time digital financial tracking systems, which supersede traditional retrospective reporting by automating budget control and minimizing human error. Furthermore, the study identifies that institutional accountability must be aggressively enforced through the establishment of independent whistleblowing systems and comprehensive financial risk management policies to proactively manage market fluctuations and deter authority abuse. To ensure execution, the research highlights that human resource development must transcend generic training by embedding strict, performance-based incentive frameworks directly tied to established efficiency targets. The novelty of this research lies in formulating an integrated, tech-driven policy framework that legally and operationally binds BLU flexibility with stringent, proactive oversight mechanisms dictated by the State Treasury Law. Ultimately, enforcing these specific, targeted mechanisms will allow BLUs to secure robust financial accountability and operational efficiency, thereby fundamentally elevating the quality of public service delivery.